The Media Framing War in Coverage of Fuel Adulteration by Pertamina: (A Comparative Study of Tempo.com and Instagram Account @TotalPolitikcom in February 2025) - Dheagatha, Dheagatha Agustina Pertiwi; Merry Frida Tri Palupi; Bambang Sigit Pramono (Kirana Publisher (KNPub), 2025)
This study discusses the media framing war in the news of fuel adulteration by Pertamina in February 2025. The main focus of the study is a comparison of framing carried out by the online media Tempo.com and the Instagram account @TotalPolitikcom. This study uses a qualitative approach with the Robert Entman (1993) framing model analysis method, and is based on the theory of media reality construction. The results of the study show that Tempo.com frames the issue structurally, with a focus on improving the monitoring system and energy policy reform. Meanwhile, @TotalPolitikcom uses emotional and populist framing, which emphasizes elite betrayal and encourages public participation through social media. The construction of reality produced by both media shows the fragmentation of public narratives in responding to strategic issues.